Proceedings of the 8th International Conference on Theory and Practice of Electronic Governance 2014
DOI: 10.1145/2691195.2691240
|View full text |Cite
|
Sign up to set email alerts
|

Open government data and the data usage for improvement of public services in the Rio de Janeiro City

Abstract: The use of Information and Communication Technologies (ICTs) for information transparency in Brazil is not recent. It is possible to highlight several strategies have emerged to promote transparency of these information. This article aims to fill a gap observed in the literature regarding the use of data and information provided by governments and used by citizens and companies from the comparison with the specialized bibliography. The methodology consists of a single case study, the city of Rio de Janeiro, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…Like the efficiency studies above, a number reported on whether initial objectives were obtained. Correa (2014) and Canares (2014) showed that governments examined were and were not compliant with transparency policies respectively, and Matheus et al (2014) gave mediocre rating to Brazilian provinces based on Berners-Lee 5-star rating. Yet, these authors all made recommendations in terms of improving multi-stakeholder relations and interactivity, which leads to the conclusion that their effectiveness measures are not adequate.…”
Section: Source: Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Like the efficiency studies above, a number reported on whether initial objectives were obtained. Correa (2014) and Canares (2014) showed that governments examined were and were not compliant with transparency policies respectively, and Matheus et al (2014) gave mediocre rating to Brazilian provinces based on Berners-Lee 5-star rating. Yet, these authors all made recommendations in terms of improving multi-stakeholder relations and interactivity, which leads to the conclusion that their effectiveness measures are not adequate.…”
Section: Source: Authorsmentioning
confidence: 99%
“…For instance, a variety of research included university students, professionals, and experts to participate in or to test initiatives (Ansal and Yildirim, 2010;Murthy et al, 2014;Wu et al, 2013). Some articles made claims about the relevance of their work to 'ordinary' citizens without speaking to them or considering the actual Internet access restrictions 'ordinary' citizens face in these countries (Matheus et al, 2014;Nugroho et al, 2015). In the education domain, openness is argued to reach students who fall through the cracks (Tagoe, 2014), but typically research examined how OER can support inclusiveness for students already in attendance (Hodgkinson-Williams and Paskevicius, 2012;Shyshkina, 2015).…”
Section: 4mentioning
confidence: 99%
“…Later this was followed by regional states and municipalities, such as Sao Paulo, Recife and Rio de Janeiro. These portals started with a limited number of datasets, and functionalities [53,54]. Over time these became more advanced.…”
Section: Open Government Data Portalmentioning
confidence: 99%
“…On the dimension "types of channels to disclose data" the following types of channels were identified: i) transparency portals [37], ii) freedom of information access (FOIA) using all kind of channels [38], iii) open government data portals [39], iv) governmental portals, v) dashboard of services advertising, vi) outdoors with accountancy expenditures data in public works, vii) public financial statements (newspaper, viii) paper based at blackboards on City Hall, ix) Internet based on portals), x) call center to provide information and xi) call center to provide access and demand to public services [40]. The channels aforementioned can use different kinds of technologies and some of them were explicated such as public financial statements, with newspaper, paper based at blackboards on City Hall and Internet based via portals.…”
Section: B Type Of Channels To Data Disclosurementioning
confidence: 99%
“…From the actors that use disclosed data, it is necessary to comprehend their interest to use the data. The scientific and practical literature [40,52,53] identified four types of interest on data usage dimension: i) Service Delivery, ii) Accountability, iii) Advocacy and iv) Participation.…”
Section: B Type Of Interest On Data Usagementioning
confidence: 99%